Psychometric Properties of the Frost Multidimensional Perfectionism Scale in Spanish Children and Adolescents. (April 2019) - Gavino, Aurora; Nogueira, Raquel; Pérez-Costillas, Lucía; Godoy, Antonio
The Frost Multidimensional Perfectionism Scale (FMPS) is one of the most used instruments to assess perfectionism. The FMPS assesses six dimensions: Concern over Mistakes (CM), Parental Expectations (EP), Parental Criticism (PC), Doubts about Actions (DA), Organization (OR), and Personal Standards (PS). CM, PE, PC, and DA are facets of a more general dimension considered Maladaptive Perfectionism. PS is frequently considered Adaptive Perfectionism. FMPS psychometric properties have been studied in adults but scarcely in children. We adapted the FMPS for Spanish children and adolescents and studied these properties in a sample of 1, 648 Spanish young people (mean age = 13.36; SD = 2.28). Multigroup confirmatory factor analyses were used to test whether the FMPS dimensions found in adults are applicable to children. Results supported this hypothesis. The FMPS dimensional structure was invariant across gender and age. FMPS subscales showed good internal consistency (Cronbach's α: .71-.92) and test–retest reliability (intraclass correlations: .70-.85). Moderate and high correlations with measures of dysfunctional beliefs, anxiety, and depression supported the validity of the FMPS scores. Results from regression equations showed that the relationship of perfectionism with anxiety and depression is mostly due to Maladaptive Perfectionism.